Fats in women’s diet and everyday life - Kiczorowska , Bożena; Samolińska, Wioletta; Klebaniuk, Renata; Szczygielska, Marlena (Polish Journal of Public Health, 2019)
Introduction. Currently, vegetable oils are used not only for consumption but also for medicinal and cosmetic purposes. They are especially eagerly used by women, although their knowledge in this field is usually insufficient. Aim. The aim of the study was to determine the dietary habits of women and to analyse the importance and position of vegetable fats in their diet and life. Another objective was to assess the level of knowledge and awareness of the health-enhancing properties of these products. Material and methods. The study involved women (n=253) aged 18-30, 31-40, and over 40 years living in Lubelskie Province, Poland. The modified questionnaire was composed of questions about their diet, regularity of meals, habits and preferences of fat intake, and motivation behind including fats in the diet or for cosmetic or medicinal applications. Results. Approximately 45% of the respondents sometimes used fats with their meals and 23% used them regularly. Fats were consumed by approximately 86% of the total number of respondents and were used for medicinal and cosmetic purposes by ca. 15.5 % and 6% of the respondents, respectively. Linseed oil (34%) and coconut oil (27%) were regarded as the most valuable fats. Butter and rapeseed oil were consumed most frequently (p<0.05). Approximately 47% of the respondents regarded refined oils as valuable products, and 40% of the respondents were aware of the harmful effects of trans fats. Conclusion. The survey indicates a necessity of implementation of educational campaigns among consumers in order to disseminate the knowledge about the role of fat in the diet and the risks associated with excessive consumption and poor quality of these products